2002
DOI: 10.1016/s0009-2509(02)00290-7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the photocatalytic degradation of formic acid in a reactor with immobilized catalyst

Abstract: A kinetic model for the photocatalytic degradation of formic acid in an immobilized system is presented, including the dependency of the reaction rate on the concentration of formic acid and oxygen, the catalyst layer thickness and the light ux. In the system some external mass transfer limitation occurs which is included in the modeling with experimentally determined values for the mass transfer coe cient of both formic acid and oxygen. The model describes the measurements well. The degradation rate appears t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 36 publications
3
50
0
1
Order By: Relevance
“…Studies by Stokke et al [11], Dijkstra et al [16], Cen et al [17], Alberci and Jardin [18], Kim and Hong [19], and Jacboy [20] reported that a UV-C-irradiated ("-max = 254 nm) reactor resulted in greater photocatalytic oxidation ofVOCs than a reactor irradiated with UV -A light ("-max = 365 nm), implying that a shorter wavelength light source (i.e., higher energy photons) is more efficient. However, interpretation of the results from these studies on the effect of wavelength of TiOz-assisted photocatalysis is confounded with the influence of light intensity as these studies were conducted either at different light intensities or the light intensity was not well defined.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Studies by Stokke et al [11], Dijkstra et al [16], Cen et al [17], Alberci and Jardin [18], Kim and Hong [19], and Jacboy [20] reported that a UV-C-irradiated ("-max = 254 nm) reactor resulted in greater photocatalytic oxidation ofVOCs than a reactor irradiated with UV -A light ("-max = 365 nm), implying that a shorter wavelength light source (i.e., higher energy photons) is more efficient. However, interpretation of the results from these studies on the effect of wavelength of TiOz-assisted photocatalysis is confounded with the influence of light intensity as these studies were conducted either at different light intensities or the light intensity was not well defined.…”
mentioning
confidence: 98%
“…Previously, UV light sources of various wavelengths ranging between 250-400 nm, and with various intensities, have been used in TiOz-catalyzed photocatalysis [1,11,[16][17][18][19][20]. Studies by Stokke et al [11], Dijkstra et al [16], Cen et al [17], Alberci and Jardin [18], Kim and Hong [19], and Jacboy [20] reported that a UV-C-irradiated ("-max = 254 nm) reactor resulted in greater photocatalytic oxidation ofVOCs than a reactor irradiated with UV -A light ("-max = 365 nm), implying that a shorter wavelength light source (i.e., higher energy photons) is more efficient.…”
mentioning
confidence: 99%
“…This mass balance shows that the TOC present in the effluent (0.007 mg C/min) was accounted for by the methanol (0.004 mg C/min) and formaldehyde (0.003 mg C/min). The lack of the presence of measurable amounts of formic acid in the effluent can be attributed to the fact that only one electron hole is necessary for the total degradation of formic acid, which, according to other literature values, results in a high apparent quantum yield (0.45) compared to other compounds (0.06-0.001) (Dijkstra et al 2002). Since formic acid is degraded directly to carbon dioxide and water, the balance of the effluent carbon should be present as carbon dioxide (Dijkstra et al 2002).…”
Section: Simultaneous Adsorption and Oxidation Of Methanolmentioning
confidence: 67%
“…Various studies have identified the existence of mass transfer limitations in many immobilized systems, such as tubular reactors [7], [8], annular reactors [9]- [11], rotating disc reactors [9], [12], and packed-bed reactors [7], [13], among others [14]. A commonly used model equation derived from first principles is a Langmuir-type equation based on volumetric flowrate Q [15], [16]:…”
Section: Introductionmentioning
confidence: 99%